Contouring of prostate tumors on multiparametric MRI: Evaluation of clinical delineations in a multicenter radiotherapy trial. Issue 2 (August 2018) - van Schie, Marcel A.; Dinh, Cuong V.; Houdt, Petra J. van; Pos, Floris J.; Heijmink, Stijn W.T.J.P.; Kerkmeijer, Linda G.W.; Kotte, Alexis N.T.J.; Oyen, Raymond; Haustermans, Karin; van der Heide, Uulke A.
Abstract: Purpose: To date no guidelines are available for contouring prostate cancer inside the gland, as visible on multiparametric (mp-) MRI. We assessed inter-institutional differences in interpretation of mp-MRI in the multicenter phase III FLAME trial. Methods: We analyzed clinical delineations on mp-MRI and clinical characteristics from 260 patients across three institutes. We performed a logistic regression analysis to examine each institute's weighting of T2w, ADC and K trans intensity maps in the delineation of the cancer. As reviewing of all delineations by an expert panel is not feasible, we made a selection based on discrepancies between a published tumor probability (TP) model and each institute's clinical delineations using Areas Under the ROC Curve (AUC) analysis. Results: Regression coefficients for the three institutes were −0.07, −0.27 and −0.11 for T2w, −1.96, −0.53 and −0.65 for ADC and 0.15, 0.20 and 0.62 for K trans, with significant differences between institutes for ADC and K trans . AUC analysis showed median AUC values of 0.92, 0.80 and 0.79. Five patients with lowest AUC values were reviewed by a uroradiologist. Conclusion: Regression coefficients revealed considerably different interpretations of mp-MRI in tumor contouring between institutes and demonstrated the need for contouring guidelines. Based on AUC values outlying delineations could efficiently be identified for review.